USING CARTOON FILM SERIES “SHAWN THE TRAIN” AS MEDIA IN TEACHING VOCABULARY TO YOUNG LEARNERS - Wafiq Aziza; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2018)
Teaching vocabulary to young learner is different and it has its own difficulty. Teacher needs good teaching skills, creativity, preparation, and patience in order to make young learners understand and comprehend each of the vocabulary given. By implementing media, teacher can create an enjoyable situations and fun activities in the classroom. Media is needed to support their activities to be interesting. Media that can be used in teaching vocabulary to young learners is cartoon film series “Shawn the Train”. Shawn the Train is a media English learning which can be implemented by teacher in teaching vocabulary to young learners around age of 5 until 9 years. Students will learn number, colors, shapes, sizes, left and right, seasons and traffic sign. Teacher begins activity by watching the cartoon film series “Shawn the Train” together with students. Then, the teacher will replay and pause the film. The teacher can pause it after Shawn tells about the vocabulary and ask the students to repeat what Shawn says in order to make the students had more practices, so that they could pronounce word correctly and remember easily.